The Algebra Textbook for the 3rd cycle of liceus (1950): reflections based on the critiques of its approval - Almeida, Mária Cristina (Historia y Memoria de la Educación, 2019)
This paper presents a work on the history of mathematics education, from a perspective that strives for a deeper reading of what has transpired in school mathematics. For this purpose, we focus on the Algebra Textbook for the 3rd cycle of liceus, approved in 1950, attempting to better understand the controversy surrounding its adoption as well as the discussion on the teaching of infinitesimal analysis in the context of this stage of secondary education. We begin by describing some opinions taken from articles published in educational and scientific journals about this textbook. In our study, we analyse two editions of the Algebra Textbook, attempting to track changes in its content. Here, we present the results of that analysis, as well as a reflection on the changes found that was written from the point of view of a teacher’s professional knowledge. The paper is based mainly on legislation, educational and scientific journals, the Algebra Textbooks for the 3rd cycle of liceus and on interviews with the author, António Augusto Lopes (1917-2015).